Optimization Of Project Duration And Constraint Resource Using Monte Carlo Method - Yap, Han Yin (Universiti Sains Malaysia, 2017)
The use of schedule monitoring and control is an important management tools and program management. Tools are available to prevent failure in construction of building that can affect the performance of the construction project. This study reviews as alternative approach to calculate the critical path in a construction project by using Monte Carlo Simulation Method to determine the criticality of the activities, forecast a most probable completion duration of a project as well as estimate the total cost of the project on a real project in Bayan Lepas, Penang. Critical Path Methods provides interrelationships of activities and scheduling of construction activities. However, CPM analysis is a deterministic process which does not account random variables. Thus, further analysis using Primavera P6 to generate CPM results as well as using Microsoft Excel to simulate the criticality of the activities and the cost of each activities. Comparing the conventional Critical Path Method with Monte Carlo Simulation Method, Monte Carlo Simulation Method shows more realistic results which close to the actual project progress. The restraint resources is estimated using Monte Carlo Simulation Method so that both result in duration wise and resource wise can be compared and optimized to provide a longest probable completion duration with minimum cost.